STUDI TENTANG MOTIVASI PEMBINAAN TILAWAH AL-QUR’AN PADA TA’LIMUL QUR’AN LIL AULAD (TQA) NURUL AL-FALAH DI KECAMATAN DUA BOCCOE KABUPATEN BONE - Martang, Martang; HM, Amir (JURNAL AL-QAYYIMAH, 2021)
AbstractThis research is a field research (fail research) with the type of qualitative research. Analyzing and researching the sources of respondents found directly in the field through the results of interviews, observations and documentation. Sources of data in this study were obtained in field studies and other supporting data. Research approaches include pedagogical, psychological and sociological. Data analysis using descriptive qualitative, the aim is to systematically describe the facts obtained from the research that took place on the object. Data processing using data reduction, data display and drawing conclusions. The results of this study indicate that the guidance of the Qur'an recitation at TQA Nurul Al-Falah, Dua Boccoe District, Bone Regency is carried out periodically and continuously, starting from basic and advanced tartil. Efforts are being made to improve the guidance of recitations by carrying out planning that is consistent with the learning tools, ranging from teachers, materials to methods. Supporting factors in enhancing the development of recitations by providing quality learning by doing motivation, improving facilities and quality. The role of the government in providing moral and material support is needed in improving the guidance of recitations in TQA Nurul Falah, Dua Boccoe District.